Fitrah sebagai Pemaknaan Humanisasi Pendidikan Islam - Amaliati, Siti; Mudlofir , Ali; Fitriani , Ely (JOM, 2024)
The aim of this research is to conduct an in-depth analysis of the concept of human fitrah as a manifestation of humanization in Islamic education that prioritizes humanitarian values. The research objectives are twofold: firstly, to explore the concept of human fitrah in the Islamic context as reflected in the Islamic education system, and secondly, to examine how the concept of fitrah in Islam can be interpreted as a foundation for humanization in Islamic education. The research methodology employed by the author is qualitative research, utilizing a literature review approach. The research findings are as follows: firstly, the concept of fitrah carries complex connotations of inherent qualities in humans, encompassing potential, abilities, and internal drives that need to be developed and directed through education. Secondly, the understanding of fitrah in the context of humanizing Islamic education emphasizes the integration of Islamic values in the educational process, encouraging individuals to possess intellectual competence, spiritual balance, and make positive contributions to society.